m6A eraser ALKBH5/treRNA1/DDX46 axis regulates BCR expression - Kapadia, Bandish; Roychowdhury, Anirban; Kayastha, Forum; Lee, Won Sok; Nanaji, Nahid; Windle, Jolene; Gartenhaus, Ronald (Neoplasia (New York, N.Y.), 2025)
•ALKBH5 and treRNA1 form a complex with DDX46 to regulate RNA m6A demethylation.•m6A demethylation by ALKBH5 enhances RNA stability and cytoplasmic export.•Loss of ALKBH5, DDX46, or treRNA1 impairs key RNA transcript expression.•ALKBH5-mediated demethylation influences BCR-related gene expression. Epitranscriptomic modifications, particularly N6-methyladenosine (m6A), have emerged as critical regulators of RNA stability, localization, and translation, shaping immune responses and tumor progression. In B-cell biology, m6A modifications influence germinal center formation and antigen-driven differentiation, underscoring their importance in immune regulation. Among m6A regulators, ALKBH5 (RNA demethylase) is pivotal in removing methylation marks and modulating gene expression in diverse cellular contexts. Despite advancements in understanding m6A dynamics, the mechanistic interplay between m6A demethylation and B-cell receptor (BCR) signaling pathways still needs to be explored. This study reveals a novel regulatory axis involving ALKBH5, treRNA1 (Translation Regulatory Long Non-Coding RNA 1), and DDX46 (RNA helicase). Upon activation signals, ALKBH5 and treRNA1 translocate to the nucleus, forming a functional complex with DDX46 to orchestrate the removal of m6A modifications on key transcripts, including those involved in BCR signaling. This demethylation enhances transcript stability and facilitates cytoplasmic export through interaction with the RNA-binding protein HuR, promoting efficient translation. Disruption of this axis, via loss of ALKBH5, DDX46, or treRNA1, led to impaired transcript processing and diminished BCR-related gene expression, highlighting the critical role of m6A demethylation in maintaining RNA dynamics. These findings uncover a previously unrecognized epitranscriptomic mechanism driven by the ALKBH5-treRNA1-DDX46 complex, with significant implications for B-cell functionality, immune regulation, and oncogenic pathways. Targeting this axis offers a promising avenue for developing therapeutic strategies in cancer and immune-related disorders where m6A dysregulation plays a central role. ALKBH5-treRNA1-DDX46 Axis: A Novel Epitranscriptomic Mechanism in B-Cell Regulation. ALKBH5 and treRNA1 translocate to the nucleus upon activation, forming a functional complex with DDX46. This complex removes m6A modifications from key BCR transcripts, enhancing their stability and promoting cytoplasmic export via HuR interaction. Efficient demethylation facilitates the translation of transcripts critical for immune regulation and oncogenic signaling. [Display omitted]